MCP-1-Induced Histamine Release from Mast Cells Is Associated with Development of Interstitial Cystitis/Bladder Pain Syndrome in Rat Models - Jianwei Lv; Yiran Huang; Shiguo Zhu; Ganggang Yang; Yujian Zhang; Jing Leng; Juanjie Bo; Dongming Liu (Mediators of Inflammation)
Objective. Interstitial cystitis/bladder pain syndrome (IC/BPS) is characterized by overexpression of monocyte chemoattractant protein-1 (MCP-1) in bladder tissues and induction of mast cell (MC) degranulation. This study was undertaken to explore the mechanism of action of MCP-1 in the development of IC/BPS. Methods. A rat model of IC/BPS was developed by perfusing bladders of nine SPF- grade female Sprague-Dawley rats with protamine sulfate and lipopolysaccharide (PS+LPS). MCP-1 and histamine levels in bladder tissue and urine were detected by immunohistochemistry and ELISA. MC degranulation was measured by immunofluorescence techniques and chemokine (C-C motif) receptor 2 (CCR2) was assayed by flow cytometry. Results. Increased MCP-1 expression in bladder tissue and elevated MCP-1 and histamine levels were observed in the urine of LS+LPS-treated rats. This was accompanied by the expression of CCR2 on MC surfaces, suggesting MCP-1 may induce MC degranulation through CCR2. Exposure to LPS stimulated MCP-1 expression in bladder epithelial cells, and exposure to MCP-1 induced histamine release from MCs. Conclusions. MCP-1 upregulation in IC/BPS is one of possible contributing factors inducing histamine release from MCs. CCR2 is involved in the process of mast cell degranulation in bladder tissues. These changes may contribute to the development of symptoms of IC/BPS.